2009
DOI: 10.2174/138161209789649475
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cell Lines in the Investigation of Pharmacogenetic Loci

Abstract: Drug response and toxicity, complex traits that are often highly varied among individuals, likely involve multiple genetic and non-genetic factors. Pharmacogenomic research aims to individualize therapy in an effort to maximize efficacy and minimize toxicity for each patient. Cell lines can be used as a model system for cellular pharmacologic effects, which include, but are not limited to, drug-induced cytotoxicity or apoptosis, biochemical effects and enzymatic reactions. Because severe toxicities may be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 137 publications
(157 reference statements)
1
21
0
Order By: Relevance
“…13,14 Of note, LCLs but even non-HapMap LCLs have been promised as useful model systems for cellular pharmacologic effects as well as biochemical effects and enzymatic reactions. 25 Several studies have been reported using LCL resources including various whole-genome approaches (e.g. GWAS) to identify novel genetic variants which subsequently were associated with anticancer-related cytotoxicity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Of note, LCLs but even non-HapMap LCLs have been promised as useful model systems for cellular pharmacologic effects as well as biochemical effects and enzymatic reactions. 25 Several studies have been reported using LCL resources including various whole-genome approaches (e.g. GWAS) to identify novel genetic variants which subsequently were associated with anticancer-related cytotoxicity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To date, genetic variants in the form of millions of single nucleotide polymorphisms (SNPs) and thousands of copy number variants (CNVs), transcription level gene expression and other phenotypic data (e.g., cellular sensitivity to drugs) have been made publicly available for many of the HapMap samples. 23,24 In this study, we set out to evaluate the extent of population differences in an important class of posttranscriptional regulators of gene expression, namely miRNAs. We explored the potential biological function of the observed differentially expressed miRNAs by comprehensively examining their relationship with target mRNAs and cellular sensitivity to chemotherapy.…”
Section: Population Differences In Microrna Expressionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) immortalized human lymphoblastoid cell lines (LCLs) from unrelated individual donors are gaining popularity as a faithful representation for the inherent human genome and epigenome natural diversity [19]. These cell lines, which are generated from peripheral blood B lymphocytes, retain most of the phenotypic properties of B lymphocytes, including the production of antibodies.…”
mentioning
confidence: 99%